2011
DOI: 10.1128/jvi.05027-11
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Infection of B Cells during Murine Gammaherpesvirus 68 Latency

Abstract: The mechanisms by which gammaherpesviruses maintain latency are unclear. Here we used a murine gammaherpesvirus model to show that previously uninfected B cells in immunocompetent mice can acquire virus during latency. In vivo depletion of T cells allowed viral reactivation, as measured by increased viral loads, but not enhanced transfer of virus to new cells. In the absence of both immune T cells and antibody following the transfer of latently infected cells into naïve animals, there was robust infection of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Mice deficient in either CD8 or CD4 T cells succumb to infection, albeit with different kinetics, and both CD8 and CD4 T cells contribute to the long-term control of viral latency (2)(3)(4)(5). In some models of viral infection, CD4 T cells are critically important for helping CD8 T cells generate optimal memory cells.…”
mentioning
confidence: 99%
“…Mice deficient in either CD8 or CD4 T cells succumb to infection, albeit with different kinetics, and both CD8 and CD4 T cells contribute to the long-term control of viral latency (2)(3)(4)(5). In some models of viral infection, CD4 T cells are critically important for helping CD8 T cells generate optimal memory cells.…”
mentioning
confidence: 99%
“…This technique has been used to demonstrate that new naïve T cells can respond to persistent viral infections (4, 7). We have recently shown that busulfan treatment of γHV68-infected mice does not affect the latent viral load or impair the pre-existing humoral and cellular immunity (3). We allowed latently-infected mice to reconstitute for up to 28 weeks then measured the phenotype of the host and donor CD8 T cells (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…In our recent report, we demonstrated that depletion of the host T cell response by anti-Thy1.2 mAb injections led to substantial reactivation of latent virus, leading to enhanced infection of the donor B cells (3). It is unknown, however, whether viral reactivation also stimulates the recruitment of naïve T cells into the ongoing response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations